Persistence of estrogenic activity in soils following land application of biosolids. (29th October 2013) - Langdon, Kate A.; Warne, Michael S.t.J.; Smernik, Ronald J.; Shareef, Ali; Kookana, Rai S.
Abstract Estrogenic compounds may enter the environment when biosolids are applied to land. In the present study, soil samples were collected over 4 mo from a field trial following addition of biosolids. The recombinant yeast estrogen screen bioassay identified estrogenic activity in the soil at all sampling times to concentrations up to 2.3 µg 17β‐estradiol equivalency/kg. The present results indicate the potential for estrogenic compounds to persist in soil following biosolids application. Environ Toxicol Chem 2014;33:26–28. © 2013 SETAC